The Effects Of Quality, Interaction, Motivation, And User-Characteristics On Students’ Satisfaction And Learning In An Open And Distance Learning Environment - Abubakar, Yunusa Abdullahi (2022)
This study deployed a proposed nomological network (a conceptual integrated model) of models and theories drawn from the DeLone and McLean Information Systems success model (D&MISS), the Theory of Transactional Distance (TTD), Self-Determination Theory (SDT) and the User Characteristics Factors to evaluate students’ satisfaction and perceived learning based on their learning experience with the integrated Learning Management System (iLMS) of the open and distance university in Nigeria.